HUBUNGAN KELENTUKAN PERGELANGAN TANGAN, POWER DAN PANJANG LENGAN DENGAN KETEPATAN SERVIS PANJANG - Mesiyani, Putri (Universitas Negeri Semarang, 2016)
The background of this research is the wrist flexibility, power arm and l arm length was essential to produce a long serve accuration. The research problem is whether there is a relationship between the wrist flexibility, power arm and arm length with a long serve accomplishments done individually or together on the club's players Tugu Muda Semarang sons ages 8-12 in 2015?  This research used a survey design with one-shot models. Retrieving data with the test method of measurement by measuring the wrist flexibility, power arm, arm length and a long serve. The research sample the club's player Tugu Muda Semarang sons ages 8-12 in 2015 amounting to 8 people while the sampling technique is total sampling. Analysis of the data used is simple and multiple regression analysis. Results of the study is of the club's player Tugu Muda Semarang sons ages 8-12 in 2015 there was a significant correlation between the wrist flexibility with the results of a long serve of 0.932, there was a significant relationship between the power arm with the results a long serve of 0.907, there was a significant arm length with the results of a long serve of 0.966 there was a significant correlation between wrist flexibility, power arm and arm length with the results a long serve of 0.979.   Based on the research results suggested to improve the ability of a long serve then the player should increase the power arm and maximize the wrist flexibility and arm length.